Three-year chronic follow-up from the pilot study of a substernal extravascular implantable cardioverter defibrillator. (19th May 2022) - Crozier, I; Haqqani, H; Kotschet, E; Shaw, D; Prabhu, A; Roubos, J; Alison, J; Melton, I; Denman, R; Lin, T; Almeida, A; Thompson, A; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Medtronic Background: The investigational Extravascular Implantable Cardioverter-Defibrillator (EV ICD) uses a substernal lead and delivers defibrillation and pacing therapies, including antitachycardia pacing (ATP). Objective: To characterize EV ICD system performance through 3 years. Methods: The prospective, first-in-human EV ICD Pilot study was conducted at 4 sites in Australia and New Zealand. ICD-indicated patients were enrolled July-December of 2018. Defibrillation testing was conducted for all patients at implant, and chronically per physician discretion. Electrical testing was conducted at pre-hospital discharge, 2 weeks, 4-6 weeks and 3 months post-implant, and every 6 months thereafter. Posture effects on pacing and sensing were evaluated through 3 months. Results: Of 26 patients enrolled, 21 underwent the EV ICD implant procedure. There were no intraprocedural complications. After successful implantation and testing, 17 of 21 patients entered chronic follow-up. 14 patients continue follow up, representing 523 patient-months. Eight elective chronic defibrillation tests converted 7 of 7 patients with ≤ 40 J (maximum energy). Five episodes of spontaneous ventricular tachycardia (VT) were detected in 1 patient and either self-terminated or successfully defibrillated with appropriate shock. Over the total course of follow-up, 3 patients received an inappropriate shock due to; lead tip displacement with subsequent P-wave oversensing; Electromagnetic interference (EMI) in a ungrounded hot-tub; and EMI while doing plumbing work on unearthed electrical pipes, resulting in an annualized inappropriate shock rate of 6.9%. Pacing capture thresholds remained stable across time (5.1 ± 2.0 V at implant and 5.5 ± 2.7 V at 3 years); similarly, R-wave amplitudes were stable across time (3.4 ±2.0 mV at implant and 4.2 ± 2.7 mV at 3 years). Pacing thresholds tended to be lowest with the patient lying on the right side and pacing threshold often increased relative to supine position for left-side, prone or bending postures. R-wave amplitude tended to be greater when bending forward. There were 10 system or procedure-related adverse events in 8 patients through 3 years, including 3 elective system removals for: a single inappropriate shock (1), chronic defibrillation testing showing no safety margin in a patient with arrhythmogenic right ventricular dysplasia (1), intolerance to ATP (1 - high pacing threshold and frequent VT). Other than the lead tip displacement within the first 3 months, no additional clinically significant lead displacements have been observed through 3 years. Conclusion: The EV ICD is a novel platform for delivering high-voltage therapy. There were no procedure and system related complications observed after the first year post-implant. Lead position and chronic system performance have generally remained stable through 3 years with a low rate of adverse events.